Singapore SMEs approach towards adopting IR4.0: a digital leadership perspective - Arumugam, Balasubramaniam (2021)
The global industries have witnessed different stages of revolution since the inception of the industrial revolution era. Industry 4.0 has been discussed as the emerging digital revolution across the economic climate based on industry experts. The global governments have allocated a significant portion of their budget to explore the possibilities and implementation of this digital disruption. Multinational corporations (MNCs) have commenced their efforts in adopting digital initiatives within their organisation due to their large division of labour and financial resources. Small Medium Enterprises (SMEs) had displayed hesitancy in adoption due to unfamiliarity and fear of failure in investment return. Singapore Government has been actively promoting digitalisation among local SMEs through various grants and initiatives. Given this background, the aim of this study is to examine the influence of digital leadership approach in preparing Singapore SMEs for Industry 4.0 to stay competitive. The digital leadership approach through Strategic Alignment and Adaptive Structuration theories have been widely discussed by researchers through the extensive literature review. The digital leadership approach combined with these theories had been set as an independent variable. The successful alignment of business and current I/T strategies based on IR 4.0 and the motivation of employees to embark on a digital transformation journey had been set as the dependent variables. The conceptual framework was established based on these variables to study Singapore SMEs’ perspective towards IR4.0. A mixed research approach was adopted. The quantitative data was collected from SME employees who are currently engaged or considering to embark on the digital transformation journey through an internet survey instrument. The qualitative data was collected from SME employers who are currently involved in the digital transformation process through a semi-interview instrument. The overall results have indicated that there is a positive correlation between the awareness of digital transformation and motivation towards digital leadership among SME employees and employers. However, there are significant challenges to implement IR4.0 initiatives as found in the study. The recommendations have been presented based on the extensive literature review and collected data analysis. SME employers need to adopt effective digital leadership practices to adopt suitable government grants and redefine their current organisational mindset towards digital transformation.